Perspektif terhadap Kawasan Bersejarah: Kategori Pengunjung berdasarkan Korelasi antara Daya Tarik dan Harapan terhadap Kawasan Braga - Levana Salsabila; Hanson Endra Kusuma (RUAS (Review of Urbanism and Architectural Studies), 2019)
The Braga area is one of the cultural heritage tourist destinations in Bandung with the attraction of its colonial architecture. The emergence of new buildings in the region is presented without giving attention to the surrounding colonial buildings. The visitor’s perspective on the Braga area is an important basis in regional growth and development. This study aims to find the perspective of visitors based on the correlation between their attraction and expectations of the Braga region. The method used in this study was mixed methods (qualitative-quantitative), and data collection was carried out using a survey through a freely distributed online questionnaire (snowball non-random sampling). The collected data is then analyzed qualitatively using content analysis and quantitatively using principal component analysis, factor analysis, and multivariate correlation analysis. The results of the study revealed the existence of two perspectives, namely appreciative and recreational. The appreciative perspective sees Braga as having an attractive heritage of historical buildings and hopes that Braga will become a conservation area. While the recreational perspective regards Braga as an entertainment area that is unique and hopes for the commodification of the Braga area.